Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0045499
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes Regulate Vascular Basement Membrane Remodeling and Govern Neutrophil Extravasation during Inflammation

Abstract: During inflammation polymorphonuclear neutrophils (PMNs) traverse venular walls, composed of the endothelium, pericyte sheath and vascular basement membrane. Compared to PMN transendothelial migration, little is known about how PMNs penetrate the latter barriers. Using mouse models and intravital microscopy, we show that migrating PMNs expand and use the low expression regions (LERs) of matrix proteins in the vascular basement membrane (BM) for their transmigration. Importantly, we demonstrate that this remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 49 publications
4
104
0
2
Order By: Relevance
“…But LPS-treated pericytes not only produce chemokines that could attract immune cells, they also overexpress adhesion molecules such as ICAM-1 and VCAM-1. Recent works have demonstrated that mouse pericytes facilitate neutrophil transmigration through postcapillary venular walls in an ICAM-1-dependent manner using a model of TNF-␣-or IL-1␤-stimulated mouse muscle in vivo (51,52). In fact, capillary and arteriolar NG2 ϩ pericytes can "instruct" extravasating neutrophils and monocytes with migratory cues (53).…”
Section: Discussionmentioning
confidence: 99%
“…But LPS-treated pericytes not only produce chemokines that could attract immune cells, they also overexpress adhesion molecules such as ICAM-1 and VCAM-1. Recent works have demonstrated that mouse pericytes facilitate neutrophil transmigration through postcapillary venular walls in an ICAM-1-dependent manner using a model of TNF-␣-or IL-1␤-stimulated mouse muscle in vivo (51,52). In fact, capillary and arteriolar NG2 ϩ pericytes can "instruct" extravasating neutrophils and monocytes with migratory cues (53).…”
Section: Discussionmentioning
confidence: 99%
“…As described previously (42), retroviral packing was performed using a combination of human 293FT cells, the packing plasmids, and the pGFP-C-shLenti-vector carrying scrambled or rat α-syn-specific shRNA (Origene Technologies). Infection of rat neuron-enriched cultures was performed overnight by adding the media collected from the transfected 293FT cell cultures to each neuron-enriched culture, along with 6 μg/mL polybrene.…”
Section: Animals Mice Deficient In Gp91mentioning
confidence: 99%
“…Transmigration of neutrophils into the surrounding tissue takes place through venules at permissive sites that lack mural cell coverage and have different basement membrane components [125][126][127][128]. Real-time imaging to monitor neutrophil transmigration in living inflamed tissue has demonstrated that, after transendothelial migration, neutrophils crawl along pericytes, which are mediated via intercellular adhesion molecule-1 (ICAM1)-Macrophage-1 antigen (Mac1) interaction [127].…”
Section: Regulation Of Leukocyte Traffickingmentioning
confidence: 99%
“…Mural cells also react to inflammatory stimuli (e.g. tumor necrosis factor) by the expansion of pericyte gaps, thus enabling neutrophil to exit these structures [127,128]. Interestingly, the expansion of gaps between pericytes was induced by neutrophil-pericyte interaction that supressed actomyosin-based contractility in pericytes [128].…”
Section: Regulation Of Leukocyte Traffickingmentioning
confidence: 99%